An Energy‐Efficient Crude Distillation Unit with a Prefractionator. Issue 3 (2nd February 2017) - Kim, Young Han
Abstract: An energy‐efficient crude distillation unit (CDU) was proposed, and its performance was evaluated and compared with that of a conventional CDU. The problem of the large energy demand associated with the single‐column operation of a conventional CDU was solved with a two‐column operation – a prefactionator and a main column – in the proposed CDU. The two‐column operation reduces feed‐tray mixing, and thus raises the thermodynamic efficiency of the CDU. The proposed unit has reduced heating and cooling duty compared with that of the conventional unit. The proposed unit also has fewer investment and utility costs. Vapor and liquid flow connections between the two columns are readily available by adjusting the difference in column operating pressure. Abstract : A crude distillation unit (CDU) is the first step in the refinery processing of crude oil and consumes a large amount of energy. To overcome this, an energy‐efficient CDU has been proposed which reduces the energy demand through a two‐column operation. In the proposed CDU, reduced feed‐tray mixing lowers heat duty and saves investment and utility costs.